Maintenance operation of fort building at Sarawak / Sudan Tugau - Tugau, Sudan (2008)
Fort Building is one of the heritages building. The fort building already has build at 100 years and more. Definition of fort is a strong or fortified place; especially: a fortified place occupied only by troops and surrounded with such works as a ditch, rampart, and parapet. The second meaning of fort is a permanent army post - often used in place names. The maintenance of the fort buildings is different. Fort Emma and Fort Margherita is under the local authority. But the Fort Sylvia is under the Tun Jugah Foundation. Today, the Fort Sylvia and Fort Margherita is became a museum. Fort Sylvia is be a Tun Jugah Museum where the fort store the things about Tun Jugah and story about the Tun Jugah. Besides that Fort Sylvia also store the story about Kapit, Sarawak. Fort Margherita is became a police museum. In Fort Margherita store the things of army such as like weapons, guns and so on.